2010
DOI: 10.1007/s00395-010-0109-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term diabetes impairs repopulation of hematopoietic progenitor cells and dysregulates the cytokine expression in the bone marrow microenvironment in mice

Abstract: Diabetes is characterized by a chronic stage of hyperglycemia associated with endothelial progenitor cell dysfunction and reduced neovascularization in response to tissue ischemia. The underlying mechanisms are not entirely clear. The bone marrow niches provide the essential microenvironment for maintenance of stem cell function in the bone marrow. A disturbed stem cell niche might lead to stem cell dysfunction, thereby, impairing progenitor cell-dependent vascular repair. Therefore, we investigated the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 51 publications
7
85
3
Order By: Relevance
“…Importantly, the presence of diabetes mellitus is associated with reduced number and function, as well as increased senescence, of stem cells. We found that in patients with acute MI and diabetes the mobilization of VSELs was impaired as compared to non-diabetics [26]. We also demonstrated that in patients with acute MI and reduced LVEF the number of circulating VSELs is reduced and negatively correlated with LVEF and troponin levels.…”
Section: Factors Affecting the Mobilization Of Vselssupporting
confidence: 52%
“…Importantly, the presence of diabetes mellitus is associated with reduced number and function, as well as increased senescence, of stem cells. We found that in patients with acute MI and diabetes the mobilization of VSELs was impaired as compared to non-diabetics [26]. We also demonstrated that in patients with acute MI and reduced LVEF the number of circulating VSELs is reduced and negatively correlated with LVEF and troponin levels.…”
Section: Factors Affecting the Mobilization Of Vselssupporting
confidence: 52%
“…29 Recently, it has been shown that long-term diabetes not only impairs repopulation of hematopoietic progenitor cells but also dysregulates the cytokine expression in the bone marrow microenvironment in mice, suggesting that diabetes alters the stem cell niche. 30 Consequently, the improvement of failed functions of endothelial mature cells and EPCs during diabetes represents the goal of future therapeutic approaches.…”
Section: Failed Angiogenesis In Metabolic Diseasesmentioning
confidence: 99%
“…Altogether, these data suggest that the hypo-perfusion caused by contraction of the vascular niche is a major determinant of stem cell reduction in BM of diabetic mice. However, in a similar study conducted by Orlandi et al in C57BL/6 STZ-induced diabetic mice, no microvascular rarefaction was observed, probably due to the different mouse strain analyzed and shorter duration of DM (80).…”
Section: Microangiopathy In Bm Of Diabetic Mice Jeopardizes Stem Cellmentioning
confidence: 87%